Modification of the inlet to the tertiary air duct in the cement kiln installation - Borsuk Grzegorz; Wydrych Jacek; Dobrowolski Bolesław (Chemical and Process Engineering)
Rotary kiln installation forms a very complex system, as it consists of various components which affect cement production. However, some problems with particle settling are encountered during operation of tertiary air installation. This paper reports on the results of a study into gas-particle flow in a tertiary air duct installation. This flow was calculated using Euler method for air motion and Lagrange method for particle motion. The results in this paper demonstrate that study focus on the tertiary air installation is a practical measure without the analysis of other processes in the rotary kiln. A solution to this problem offers several alternatives of modifying the inlet to the tertiary air duct. As a result of numerical calculations, we demonstrate the influence of geometry of a rotary kiln modification on the number of large particles transported in the tertiary air duct. The results indicate that in order to reduce large particles, rotary kiln head geometry needs to be modified, and a particle settler should be installed at its outlet.